Comparison of clinical efficacy and secondary infections between conventional-dose and high-dose glucocorticoid in hemorrhagic fever with renal syndrome: a dual-center retrospective cohort study - Denghui Yu; Jiayi Zhan; Hong Du; Pingping Zhu; Haifeng Hu; Hongkai Xu; Ludan Zhang; Fei Hu; Zhanhu Bi; Xiaofei Yang; Yanping Li; Jianqi Lian (BMC Infectious Diseases)
Abstract Background Glucocorticoids (GC) are commonly administered during the febrile and hypotensive phases of hemorrhagic fever with renal syndrome (HFRS) to alleviate inflammation and capillary leakage. However, clinical dosing regimens show marked variability. This study aims to evaluate the clinical necessity of high-dose GC therapy during the acute phase of HFRS. Methods A retrospective study involving 807 HFRS patients admitted to two centers was conducted. Propensity score matching and multivariate logistic regression models were used to compare the effects of conventional-dose and high-dose GC on HFRS treatment outcomes and the risk of secondary infections. Results There were no significant differences in hospital stay, acute-phase fluid requirement, renal replacement rates, mechanical ventilation needs, severe hemorrhagic complications, or mortality between HFRS patients receiving conventional or high-dose GC. Among patients with a shock phase, the secondary infections rate was significantly higher with high-dose GC compared to conventional-dose (43.48% vs. 23.91%, p = 0.005). High-dose GC emerged as an independent risk factor for secondary infections (OR 2.88, 95%CI 1.41–5.88), while prophylactic antibiotics served as an independent protective factor (OR 0.29, 95%CI 0.13–0.65). In patients without a shock phase, no significant difference was observed in the effect of the two GC doses on secondary infections. However, GC therapy ≥ 4 days was an independent risk factor (OR 2.54, 95%CI 1.21–5.37). Conclusions High-dose GC show no superiority over conventional-dose GC on hospital stay, acute-phase fluid requirement, renal replacement rates, mechanical ventilation needs, severe hemorrhagic complications, or mortality. High-dose GC may increase secondary infections in HFRS patients with a shock phase. GC therapy ≥ 4 days may also increase secondary infections in patients without a shock phase.